Quest for good quality medicines in hospitals: a structured approach - Kairi, Jayant Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Patients use medicines to gain speedy recovery from illness or to maintain wellbeing under the care of their physicians. For chronic illnesses, the pharmacotherapy may continue for the entire lifetime. Significant expenditure is incurred in sustaining this pharmacotherapy. Quite expectedly, the patients are concerned about the quality of medicines that they receive and consume. In recent times, the quality concerns have increased phenomenally due to media hype and overexposure all around. Ensuring quality of medicines in developing countries is not easy. Multi-pronged approaches are needed to ensure procurement of good quality medicines by institutional buyers. However, ensuring the procurement of good quality medicines is not enough. The quality of medicines has to be maintained till their consumption by patients and a rational, scientific method has to be adopted to ensure this goal. A structured approach in ensuring good quality medicines for optimum pharmacotherapy is being presented in this review.